2020
DOI: 10.1177/0960327120954522
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of Omega-3 PUFAs against acute paracetamol-induced hepatic injury confirmed by FTIR

Abstract: Acute paracetamol over dose-induced hepatotoxicity is considered an important medical hazard especially among women. Omega-3 long-chain polyunsaturated fatty acids (Omega-3 PUFAs) daily doses are nowadays recommended for their antioxidant and anti-inflammatory potentials. Fourier transform infrared (FTIR) spectroscopy is considered a reliable method in analyzing cellular alterations and is now efficiently used to diagnose several diseases and the efficacy of drugs even in the early stages. The aim of our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…2,8 The growing demand for natural and nutritious foods without chemical additives stimulates many researchers to investigate the hepatoprotective effects of natural compounds, such as naturally occurring antioxidants that cause a range of biological activities. 9 As ROS are activation candidate driver for HSCs and up-regulator of collagen, the anti-oxidant supplements can emerge as potentially anti-fibrotic agents either by protecting hepatocytes from ROS, or by inhibiting hepatic stellate cell activation. 10,11 Carvacrol is a common monoterpene phenol that is present in several significant oil species.…”
Section: Introductionmentioning
confidence: 99%
“…2,8 The growing demand for natural and nutritious foods without chemical additives stimulates many researchers to investigate the hepatoprotective effects of natural compounds, such as naturally occurring antioxidants that cause a range of biological activities. 9 As ROS are activation candidate driver for HSCs and up-regulator of collagen, the anti-oxidant supplements can emerge as potentially anti-fibrotic agents either by protecting hepatocytes from ROS, or by inhibiting hepatic stellate cell activation. 10,11 Carvacrol is a common monoterpene phenol that is present in several significant oil species.…”
Section: Introductionmentioning
confidence: 99%
“…However, improvement in these biomarkers after extract-based interventions may be attributed to their bioactive moieties including phenolic compounds and essential fatty acids (Banji et al, 2011;Borashan et al, 2008;El-Gendy et al, 2020;Hussain et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the biological evaluation, the dose of TiO 2 -NPs was selected based on the previous work of Shakeel et al. (2016) ; however, the dose of EMFO was based on the work of El-Gendy et al. (2021) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was reported that diet supplemented with ω-3 PUFAs increased cytochrome P450 2El (CYP2E1) content in the liver ( Maksymchuk, 2014 ) with no significant changes in the lipid peroxidation or the balance between the hepatic prooxidant/antioxidant ( Maksymchuk et al., 2015 ) Our results showed that EMFO diminished the increase of cytokines (AFP, TNF-α and CEA) levels in animals received TiO 2 -NPs. In this concern, previous reports indicated that ω-3 PUFAs suppress the arachidonic acid transformation into the pro-inflammatory eicosanoids via different pathways including cyclooxygenase-2 and 5-lipoxygenase through inhibiting eicosanoid-generating enzymes activity or competing with the substrate in addition to the effect of their metabolites such as protectins and resolvins in hindering the steatosis and inflammation ( El-Gendy et al., 2021 ; Wu et al., 2019 ). Moreover, ω-3 PUFAs were found to decrease the inflammation via the reduction of NF-kB concentration which in turn decreases the production of the inflammatory cytokines such as IL-1b and TNF-a beside the reduction of arachidonic acid-derived eicosanoids, consequently protect against the oxidative stress ( Scorletti and Byrne, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation